EVALUASI PEMILU SERENTAK TAHUN 2014 DI PROVINSI LAMPUNG - rudy rudy; martha riananda; utia meylina (Fiat Justisia: Jurnal Ilmu Hukum, 2014)
This research aims to find a model of electoral implementation simultaneously in Indonesia, through the elections of regional heads of Lampung province as a form of legislative elections, and the election of regional heads were held simultaneously on April 9, 2014. This research uses case approach and statute approach. The research found that there were drawbacks on the election of regional heads in Lampung province, one of them was the postponement of the election. Keywords: Election Evaluation of 2014, and Lampung Province